Perspectives on interdisciplinary undergraduate research. Issue 3 (27th May 2018) - Ülkü, M. Ali; Karkowski, Andrea M.; Lahm, Terry D.
Abstract: Undergraduate Research (UR) provides deeper experiential learning opportunities for students while increasing their self-efficacy, academic success and motivation to pursue graduate studies. Many real-world problems require an integrated solution and collaboration across different disciplines; therefore, it is important that students develop skills to work across disciplines on challenging research problems. As types and complexity of UR increase, Interdisciplinary Undergraduate Research (IDUR) has become more prevalent, but little is known about it. We define IDUR as "student-faculty collaboration to examine, increase, and share new knowledge or works relevant to research questions the investigation of which necessitates an interdisciplinary approach". From the faculty perspective, and based on the results of a national sample of higher learning institutions in the U.S., we outline the enablers of and barriers to IDUR and provide quantitative and qualitative insights. Survey results show that, irrespective of the size of the institution at which they work, faculty members value mentoring students conducting IDUR although it brings with it some challenges. Our findings may help institutions better facilitate IDUR projects and inform faculty development opportunities that deepen student learning and retention via enhanced curricula in which IDUR is embedded.